Enseñanza por correspondencia - Klus, John (My University, 1975)
Since you are interested in teaching or writing and independent study course, it is important for you to know that an instructor may or may not have written the course he will write. As an educator competent in your field of knowledge, you are undoubtedly anxious to achieve top-level performance. These guidelines will supply you with ideas, background, and hints that will help you to proceed with a measure of confidence and effectiveness.
Keywords: learning theory; marketing strateggy; learning process; dimensions of change; purpose and methods